Medicinal use of plants by the peasant community of San Jacinto, northern Colombia Medicinal use of plants by the peasant community of San Jacinto, northern Colombia - Bonzani Renée M. (Caldasia)
I studied the medicinal use of plants by the peasant community of the town of San Jacinto, located in the savanna of Bolívar, northern Colombia. Fifty-five families, 138 genera, and 118 species were scientifically identified from 249 specimens collected of the modern-day vegetation of San Jacinto. From these, 198 uses were recorded for 190 (76%) of the specimens. The 54 uses recorded for human medicine (27%) and the five uses recorded for animal medicine (2%) are discussed. Vernacular names, parts used, method of preparation, and medicinal uses are listed. Se presenta un estudio etnobotánico de la comunidad campesina del pueblo de San Jacinto, localizado en las sabanas de Bolívar, norte de Colombia. Se identificaron científicamente 55 familias, 138 géneros, y 118 especies con base en 249 especímenes recolectados de la vegetación de San Jacinto. De esos, se establecieron 198 usos para 190 (76%) especímenes. Se presentan 54 usos para medicina humana (27%) y cinco usos para medicina animal (2%). Se listan nombres vernáculos, partes usadas, método de preparación, y usos medicinales.